Giant aortic aneurysm in a child with Takayasu arteritis. (14th September 2015) - Halaweish, Ihab; Patel, Himanshu; Si, Ming-Sing
Abstract: Takayasu arteritis is a chronic, idiopathic, granulomatous vasculitis involving the aorta, its major branches, and occasionally the pulmonary arteries. Although rare in children, it is the third most common vasculitis in the paediatric population. Although aneurysmal disease has been reported in adults with Takayasu arteritis, it is a rare entity in children. We present the case of a 10-year-old boy with a giant ascending and arch aneurysm that necessitated follow-up surgery for a new aneurysm and occlusive disease. This is also the first published case involving endovascular aortic graft placement for the management of vascular sequela of Takayasu arteritis in a child.